1998
DOI: 10.1097/00007632-199807150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Claim Rates of Compensable Back Injuries by Age, Gender, Occupation, and Industry

Abstract: The relative risk of compensable back injury is generally higher for females in white collar occupations, higher for males in blue collar occupations and approximately equal in service occupations. Although the risk of back injury is related to occupation, the same occupational factors do not operate as a barrier to return to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 24 publications
6
41
1
2
Order By: Relevance
“…Most of the studies that assess the indirect costs of back problems focus on the time lost to work absence as the main cost of back problems [1,5,9,12,13,28]. This study adds to this international literature by quantifying the amount of wealth lost by individuals who have retired early due to back problems: a previously unexplored area on the costs of this condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies that assess the indirect costs of back problems focus on the time lost to work absence as the main cost of back problems [1,5,9,12,13,28]. This study adds to this international literature by quantifying the amount of wealth lost by individuals who have retired early due to back problems: a previously unexplored area on the costs of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies undertaken in Australia and Europe have attributed most of these indirect costs to the work absenteeism caused by back problems [1,5,7,[9][10][11][12][13][14]. Extreme back pain can lead to early retirement, and 41.4% of Australians aged 45-64 years who identify back pain as their main health problem are not in the workforce [15].…”
Section: Introductionmentioning
confidence: 99%
“…A maior ocorrência de incapacidade para o trabalho entre as mulheres e o aumento de tal ocorrência com a idade, encontrada neste estudo, é confirmada tanto pela literatura nacional 3,7,8,9 quanto internacional 4,11,19,20,21,22,23 .…”
Section: Discussionunclassified
“…Results from this previous study indicated that workers employed in public administration, construction, finance, transport, and education were less likely to return to work than those in healthcare occupations. Studies by Gluck et al (28) and Oleinick et al (29), utilizing large cohorts of Michigan workers' compensation claims for back injuries, found that blue-collar workers returned to work earlier than their white-collar counterparts or those in service occupations. However, some studies found the opposite (34).…”
Section: Occupationmentioning
confidence: 99%
“…Several studies (14,(26)(27)(28)(29)(30) have examined the association between gender and RTW outcomes, although no consistent trend has emerged. A review by Crook et al (6), for example, found that women were more likely to have increased disability following low-back injury.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%